The Effect Of Gcg Mechanism And Company Size On The Financial Performance Of Manufacturing Companies In The Automotive Sub Sector In The Indonesia Stock Exchange - Febby Putri Anasya Lubis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2022)
This study aims to determine the effect of the Good Corporate Governance mechanism in which the board of commissioners, board of directors, company size as the independent variable and financial performance as measured by return on assets as the dependent variable. Data was collected by analyzing financial statement documents and annual reports and then processed using the SPSS version 25 application. The results of data analysis showed that the board of commissioners, board of directors, and company size had no significant effect on the company's financial performance. The company's board of commissioners is expected to work effectively in supervising the board of directors in running the company so that good corporate governance can be carried out properly and have a positive influence on the company's financial performance so that the company can grow and achieve the predetermined targets and evaluate the performance of the board of commissioners, and the board of directors to examine the level of performance, integrity and contribution to its duties and responsibilities. Companies are also expected to develop or increase total assets in order to increase the size of the company which can have an impact on financial performance.